2021
DOI: 10.1177/00221678211023663
|View full text |Cite
|
Sign up to set email alerts
|

Scaling Up: Multisite Open-Label Clinical Trials of MDMA-Assisted Therapy for Severe Posttraumatic Stress Disorder

Abstract: Background: Posttraumatic stress disorder (PTSD) is a debilitating mental health condition associated with serious adverse health outcomes and functional impairment. Previous MDMA–assisted therapy (MDMA-AT) studies have shown promising results in single site studies. Two open-label studies tested this modality in multisite clinical trials to assess the feasibility of scaling this manualized therapy across 14 North American sites. Method: Cotherapist dyads were trained in the manualized MDMA-AT protocol and adm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 31 publications
0
15
0
Order By: Relevance
“…Findings from two multisite Phase 2 open-label lead-in trials (NCT03282123, NCT03485287; Wang et al, 2021) and the first Phase 3 randomized, blinded placebo-controlled trial (NCT03537014; Mitchell et al, 2021) corroborated efficacy and safety findings observed in Phase 2 trials. Wang et al (2021) found significant improvements in PTSD symptoms after three dosing sessions at the primary endpoint of 18 weeks post-baseline in 37 participants, with 76% no longer meeting criteria for PTSD. Mitchell et al (2021) found that the MDMA-AT group ( n = 46) reported significantly greater reductions in PTSD symptoms at primary endpoint compared to the placebo-assisted therapy (Placebo-AT) group ( n = 44).…”
Section: Introductionmentioning
confidence: 62%
See 2 more Smart Citations
“…Findings from two multisite Phase 2 open-label lead-in trials (NCT03282123, NCT03485287; Wang et al, 2021) and the first Phase 3 randomized, blinded placebo-controlled trial (NCT03537014; Mitchell et al, 2021) corroborated efficacy and safety findings observed in Phase 2 trials. Wang et al (2021) found significant improvements in PTSD symptoms after three dosing sessions at the primary endpoint of 18 weeks post-baseline in 37 participants, with 76% no longer meeting criteria for PTSD. Mitchell et al (2021) found that the MDMA-AT group ( n = 46) reported significantly greater reductions in PTSD symptoms at primary endpoint compared to the placebo-assisted therapy (Placebo-AT) group ( n = 44).…”
Section: Introductionmentioning
confidence: 62%
“…A thorough description of the procedures for preparatory, dosing, and integration sessions in the MDMA-AT protocol can be found in Wang et al (2021) and Mitchell et al (2021).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…3,4-methylenedioxymethamphetamine-assisted therapy (MDMA-AT) is hypothesized to reduce the fear response associated with re-experiencing traumatic memories, and therefore may facilitate tolerable processing of traumatic content in patients with PTSD (Mithoefer et al 2011). Phase 2 and 3 trials have demonstrated promise for MDMA-AT as a viable treatment for PTSD (Mitchell et al 2021; Mithoefer et al 2019; Wang et al 2021; Jerome et al 2020). In healthy individuals, acute administration of MDMA has been shown to enhance positive and reduce negative affect during the recollection of autobiographical memories, while preserving vividness and emotional intensity (Carhart-Harris et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Phase 2 and 3 trials have demonstrated promise for MDMA-AT as a viable treatment for PTSD (Mitchell et al 2021;Mithoefer et al 2019;Wang et al 2021;Jerome et al 2020). In healthy individuals, acute administration of MDMA has been shown to enhance positive and reduce negative affect during the recollection of autobiographical memories, while preserving vividness and emotional intensity (Carhart-Harris et al 2014).…”
Section: Introductionmentioning
confidence: 99%